Contribuição ao estudo das células a combustível: síntese e caracterização do monômero 2,2'-dialilbisfenol-A (ABFA) para a obtenção de membranas trocadoras de prótons baseadas em poli(arileno éter sulfona)s sulfonadas reticuladas - Julio Cesar de Souza (2010)
In the present work, a methodology of synthesis and characterization of the monomer 2,2- dialylbisphenol A ABFA was developed, aiming at getting a precursor, with adequate purity, for obtaining cross-linked membranes based on sulfonated poly(arylene ether sulfone)s. The monomer synthesis involved the synthesis of 2,2-Bis(4- alyloxiphenyl)propane (Bisphenol A, dialyl ether - BFAAE), from Bisphenol A BFA, followed by Claisen rearrangement of BFAAE compound, for the production of the target compound 2,2- dialylbisphenol A (ABFA). All the compounds, reagent BFA and obtained products, intermediate product BFAAE and final product ABFA, were characterized by the following techniques: FTIR (Fourier Transform infrared spectroscopy), TGA (Thermo-gravimetric analysis) and HPLC (High-performance liquid chromatography). The compound BFAAE was obtained with a yield of 94,50% and a purity of 97,32%, the latter characterized by TGA and by HPLC. The structure of the product was confirmed by FTIR. The thermal Claisen rearrangement process was conducted by using Differential Scanning Calorimetry DSC technique, from a factorial experiment planning, with two factors and three levels, with temperature and time being the variables. Spectroscopic analysis by FTIR, thermo-gravimetric analysis and HPLC were used for monitoring the Claisen rearrangement and for the characterization of the final product ABFA. The best results yield an ABFA purity between 85 and 90%, approximately, for 220oC/60min, 230oC/30min e 210oC/90min conditions. The obtained results suggest that, in the studied range, polymerization and degradation of the monomer ABFA occur, simultaneously to its formation.